MODELING THE ECOSYSTEM OF OPEN SCIENCE FOR THE PROFESSIONAL DEVELOPMENT AND ACTIVITY OF TEACHERS - Nosenko, Yuliia (Physical and Mathematical Education, 2023)
Formulation of the problem. The development of digital tools, cloud-oriented systems, contributes to increasing the accessibility of achievements of open science, reveals new opportunities for specialists in various fields of activity, including teachers of general secondary schools. Thus, cloud-based open science services have the potential to significantly improve the professional development of teachers by giving them access to a large number of resources, tools and opportunities to improve the quality of learning and teaching. Materials and methods. Theoretical methods are applied, in particular, analysis of research works of domestic and foreign researchers, experts, analysis of international documents, recommendations. Results. A model of the ecosystem of open science has been developed, which contains: principles and factors that will contribute to its successful implementation; facilitators who are involved in the processes of introducing open science; beneficiaries - subjects who will get the maximum benefit from it; e-infrastructure. The possibilities of using open science in the professional development and activities of teachers have been determined; opportunities and advantages of cloud-oriented services of open science for the professional development of teachers have been defined. The challenges of open science and factors for overcoming obstacles on the way to its introduction are substantiated. Recommendations for the development of the open science ecosystem have been developed, which can be used both to spread the principles of open science in general and to improve the professional development and activities of teachers in particular. Conclusions. Today, open science is an integral element of the development of the modern globalized world, which contributes to increasing the quality, transparency and credibility of scientific research. Its implementation and development became possible due to the widespread use of digital tools, in particular cloud-oriented services and systems. For a teacher, the use of cloud-oriented services of open science opens up the potential for professional development, providing access to a large number of resources, tools and opportunities for improving the quality of learning and teaching. At the same time, the success of the modelling and implementation of the ecosystem of open science depends on the coherence and effectiveness of the interaction of various subjects of open science - from politicians to educators.